Correction: High yielding synthesis of 2, 2′-bipyridine macrocycles, versatile intermediates in the synthesis of rotaxanes. Issue 6 (21st April 2016) - Lewis, J. E. M.; Bordoli, R. J.; Denis, M.; Fletcher, C. J.; Galli, M.; Neal, E. A.; Rochette, E. M.; Goldup, S. M.
Abstract : Correction for 'High yielding synthesis of 2, 2′-bipyridine macrocycles, versatile intermediates in the synthesis of rotaxanes' by J. E. M. Lewis et al., Chem. Sci., 2016, DOI: 10.1039/c6sc00011h.